2009
DOI: 10.1167/iovs.08-2907
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Receptor-Activation: Retina Protected from Ischemic Injury

Abstract: PURPOSE.In nonocular systems, activation of opioid receptors has been shown to ameliorate tissue damage induced by ischemic stress. The current study was an investigation of whether opioid receptors activated by endogenous or exogenous agonists can ameliorate ischemic retinal injury. METHODS. In an investigation of whether endogenous opioid receptor-activation reduces ischemic injury, the effects of the opioid antagonist naloxone (3 mg/kg; IP) on retinal neuroprotection induced by ischemic preconditioning (IPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 44 publications
0
58
0
Order By: Relevance
“…In the eye, activation of opioid receptors has been implicated in the regulation of iris function, accommodative power, regulation of aqueous humor dynamics (e.g., IOP), corneal wound healing, retinal development, and retina neuroprotection. 15,17,[21][22][23] d-opioid receptors (also known as DOR or DOP receptors in the International Union of Basic and Clinical Pharmacology [IUPHAR] nomenclature) are increasingly attractive due to their therapeutic potential. Along with the development of highly selective d-opioid receptor agonists and rapid progress in mouse mutagenesis approaches targeting the d-opioid receptor gene (Oprd1), novel functions of d-opioid receptors have emerged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the eye, activation of opioid receptors has been implicated in the regulation of iris function, accommodative power, regulation of aqueous humor dynamics (e.g., IOP), corneal wound healing, retinal development, and retina neuroprotection. 15,17,[21][22][23] d-opioid receptors (also known as DOR or DOP receptors in the International Union of Basic and Clinical Pharmacology [IUPHAR] nomenclature) are increasingly attractive due to their therapeutic potential. Along with the development of highly selective d-opioid receptor agonists and rapid progress in mouse mutagenesis approaches targeting the d-opioid receptor gene (Oprd1), novel functions of d-opioid receptors have emerged.…”
Section: Discussionmentioning
confidence: 99%
“…15 After removing the anterior segment of the eye and the lens, eyes, and isolated optic nerves were fixed in 4% PFA for 4 hours, then cryoprotected in 25% sucrose solution overnight at 48C. The eyecups and optic nerves were washed in ice cold PBS and frozen in optimal cutting temperature compound embedding medium over dry ice.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the role of opioid peptides in retinal ischemia, it has been reported that activation of opioid receptors facilitates the development of ischemic preconditioning within the retina and reduces the ischemic damage to the retina [70]. Recent evidence also demonstrates that activation of one or more opioid receptors can reduce the effects of ischemia-reperfusion injury by the suppression of tumor necrosis factor-α production [71].…”
Section: Neuropeptides As Anti-ischemic Agentsmentioning
confidence: 99%
“…The IR model has been widely used for studying retinal neuronal cell damage after ischaemic insult and consists of transient ischaemia followed by natural reperfusion leading to an inflammatory and neurodegenerative response in the intact retina (Osborne et al, 2004). Histologic analysis demonstrated that the IR injury causes selective neuronal loss indicated by reduced thickness of retinal layers including the ganglion cell layer, inner nuclear layer, and inner plexiform layer (Husain et al, 2009). A recent study demonstrated that IR also induced vascular abnormalities such as capillary dropout after 8 to 14 days of reperfusion and concluded that these vascular changes occurred after neuronal loss (Zheng et al, 2007).…”
Section: Introductionmentioning
confidence: 99%